2018
DOI: 10.1126/scitranslmed.aao4521
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 agonists induce transient viremia and reduce the viral reservoir in SIV-infected rhesus macaques on antiretroviral therapy

Abstract: Antiretroviral therapy (ART) can halt HIV-1 replication but fails to target the long-lived latent viral reservoir. Several pharmacological compounds have been evaluated for their ability to reverse HIV-1 latency, but none has demonstrably reduced the latent HIV-1 reservoir or affected viral rebound after the interruption of ART. We evaluated orally administered selective Toll-like receptor 7 (TLR7) agonists GS-986 and GS-9620 for their ability to induce transient viremia in rhesus macaques infected with simian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
137
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(155 citation statements)
references
References 43 publications
11
137
1
Order By: Relevance
“…In the first study, the TLR7-agonist was given to SIV-infected macaques during suppressive ART, and later all treatments were stopped. 137 Most animals rebounded in both treatment (TLR7 + ART) and control (ART only) groups, and mathematical modeling of rebound kinetics showed that rebound trajectories were altered slightly in groups receiving the TLR7 agonist in a way that suggested a partial reduction in the latent reservoir along with alterations to target cell levels and viral immune responses. 137 Consistent with these suggestions, many animals experienced transient increases in viral load during TLR7-agonist administration, despite ART, suggesting that this therapy had an unexpected latency-reversing effect, and two of the thirteen animals in the intervention group never had detectable viremia after therapy cessation.…”
Section: What Can Viral Dynamics Tell Us About the Mechanism Of Actmentioning
confidence: 96%
See 1 more Smart Citation
“…In the first study, the TLR7-agonist was given to SIV-infected macaques during suppressive ART, and later all treatments were stopped. 137 Most animals rebounded in both treatment (TLR7 + ART) and control (ART only) groups, and mathematical modeling of rebound kinetics showed that rebound trajectories were altered slightly in groups receiving the TLR7 agonist in a way that suggested a partial reduction in the latent reservoir along with alterations to target cell levels and viral immune responses. 137 Consistent with these suggestions, many animals experienced transient increases in viral load during TLR7-agonist administration, despite ART, suggesting that this therapy had an unexpected latency-reversing effect, and two of the thirteen animals in the intervention group never had detectable viremia after therapy cessation.…”
Section: What Can Viral Dynamics Tell Us About the Mechanism Of Actmentioning
confidence: 96%
“…The main drug of interest in these studies was an agonist of Toll‐like receptor 7 (TLR7), which is involved in the innate immune system response to viral infections. In the first study, the TLR7‐agonist was given to SIV‐infected macaques during suppressive ART, and later all treatments were stopped . Most animals rebounded in both treatment (TLR7 + ART) and control (ART only) groups, and mathematical modeling of rebound kinetics showed that rebound trajectories were altered slightly in groups receiving the TLR7 agonist in a way that suggested a partial reduction in the latent reservoir along with alterations to target cell levels and viral immune responses .…”
Section: Modeling Novel Therapies To Perturb Latent Infection or Boosmentioning
confidence: 99%
“…The dose regimen was also associated with activation of lymphocytes (T, NK, and B cells) and a reduction in SIV DNA in cells from the peripheral blood, lymph nodes, and gastrointestinal tract. When antiretroviral therapy ceased, 2 out of 13 treated macaques did not showrebound of virus and remained virus-free and disease-free for more than 2 years[73]. In the same study, the depletion of CD8 cells did not induced a rebound of the SIV RNA in the 2 aviremic macaques.…”
mentioning
confidence: 72%
“…Dual TLR2 and TLR7 agonists such as CL413 have shown potent NF-κB-mediated HIV-1 reactivation that unfortunately is also accompanied by proinflammatory release of TFNα [101]. In rhesus macaques infected with simian immunodeficiency virus (SIV) and in HIV-infected individuals, both on ART, the administration of the TLR7 agonists GS-986 and GS-9620 led to significant increases in plasma SIV and HIV RNA, respectively, consistent with latency reversal [102,103]. These TLR agonists are also being tested in combination with various therapeutic vaccines.…”
Section: Toll-like Receptor (Tlr) Agonistsmentioning
confidence: 94%